A widened pulse pressure: a potential valuable prognostic indicator of mortality in patients with sepsis - Hassan Al-khalisy; Ivan Nikiforov; Manjit Jhajj; Namratha Kodali; Pramil Cheriyath (Greater Baltimore Medical Center, 2015)
Background: Sepsis is one of the leading causes of death in the United States and the most common cause of death among critically ill patients in non-coronary intensive care units. Previous studies have showed pulse pressure (PP) to be a predictor of fluid responsiveness in patients with sepsis. Additionally, previous studies have correlated PP to cardiovascular risk factors and increase in mortality in end-stage renal disease patients. Objectives: To determine the correlation between PP and mortality in patients with sepsis. Methods: A retrospective review was conducted on 5,003 patients admitted with the diagnosis of sepsis using ICD-9 codes during the time period from January 2010 to December 2014 at two community-based hospitals in central Pennsylvania. Results: Our study findings showed significant decrease in the mortality when the PP was greater than 70 mmHg of patients with sepsis (p-value: 0.0003, odds ratio: 0.67, 95% confidence limit: 0.54-0.83). Conclusion: Based on our findings, we suggest that PP could be a valuable clinical tool in the early assessment of patients admitted with sepsis and could be used as a prognostic factor to assess and implement management therapy for the patients with sepsis.